An experimental investigation of the acquisition of Nd by authigenic phases of marine sediments. (15th May 2021) - Patton, Genna M.; Francois, Roger; Weis, Dominique; Hathorne, Ed; Gutjahr, Marcus; Frank, Martin; Gordon, Kathy
Abstract: The neodymium isotope composition ( ɛ Nd ) of authigenic phases in marine sediment is widely used to reconstruct the origin and mixing of water masses of overlying seawater through time. However, at some locations in the modern ocean, the ɛ Nd of authigenic phases in surface sediment is not consistent with that of local seawater, raising concerns about its current interpretation as a paleotracer of water masses. To further investigate this question, we conducted a laboratory-based incubation experiment with a Mn-oxide phase placed at the sediment–water interface of multicores to assess the extent to which the authigenic phase records seawater ɛ Nd . Multicores were collected from the Strait of Georgia (SoG), which is a relatively deep coastal waterway with high sedimentation rates, oxygenated surface sediments, and active macrofauna, separating the mainland coast of British Columbia and Vancouver Island. Manganese oxide-coated XAD resin beads were placed at the sediment surface and the cores were incubated for 6 months in a tank filled with SoG seawater spiked with 150 Nd. While the ɛ Nd of the Mn-oxide coated resin (−4.0) was similar to that of SoG seawater used for the incubation (−3.7), the 150 Nd/ 144 Nd of the Mn-oxide phase measured after the incubation indicates that, under our experimental conditions, a minimum of 83% of the Nd associated with the Mn-oxide phase is not sourced from seawater, but from pore water. The 150 Nd/ 144 Nd ratio of the Mn-oxide resin is necessary to determine the predominant source of Nd to the resin because the ɛ Nd of SoG pore water (−3.9) is within analytical error of seawater (−3.7). Using field data and constraints from the Nd mass balance during the incubation, we conclude that the similarity of ɛ Nd in pore water and seawater in the SoG is fortuitous and not a result of a top-down or bottom-up control. Although the setting of our sediments is not directly comparable to open ocean locations, this study raises concerns about the use of ɛ Nd in paleocirculation studies, and points to the necessity of elucidating the factors controlling local lithogenic dissolution in pore waters as a prerequisite for the correct interpretation of ɛ Nd in the authigenic phases of marine sediments.